Emvododstat, a Potent Dihydroorotate Dehydrogenase Inhibitor, Is Effective in Preclinical Models of Acute Myeloid Leukemia - Branstrom, Arthur; Cao, Liangxian; Furia, Bansri; Trotta, Christopher; Santaguida, Marianne; Graci, Jason D.; Colacino, Joseph M.; Ray, Balmiki; Li, Wencheng; Sheedy, Josephine; Mollin, Anna; Yeh, Shirley; et al. (Frontiers in Oncology, 2022)
Blocking the pyrimidine nucleotide de novo synthesis pathway by inhibiting dihydroorotate dehydrogenase (DHODH) results in the cell cycle arrest and/or differentiation of rapidly proliferating cells including activated lymphocytes, cancer cells, or virally infected cells. Emvododstat (PTC299) is an orally bioavailable small molecule that inhibits DHODH. We evaluated the potential for emvododstat to inhibit the progression of acute myeloid leukemia (AML) using several in vitro and in vivo models of the disease. Broad potent activity was demonstrated against multiple AML cell lines, AML blasts cultured ex vivo from patient blood samples, and AML tumor models including patient-derived xenograft models. Emvododstat induced differentiation, cytotoxicity, or both in primary AML patient blasts cultured ex vivo with 8 of 10 samples showing sensitivity. AML cells with diverse driver mutations were sensitive, suggesting the potential of emvododstat for broad therapeutic application. AML cell lines that are not sensitive to emvododstat are likely to be more reliant on the salvage pathway than on de novo synthesis of pyrimidine nucleotides. Pharmacokinetic experiments in rhesus monkeys demonstrated that emvododstat levels rose rapidly after oral administration, peaking about 2 hours post-dosing. This was associated with an increase in the levels of dihydroorotate (DHO), the substrate for DHODH, within 2 hours of dosing indicating that DHODH inhibition is rapid. DHO levels declined as drug levels declined, consistent with the reversibility of DHODH inhibition by emvododstat. These preclinical findings provide a rationale for clinical evaluation of emvododstat in an ongoing Phase 1 study of patients with relapsed/refractory acute leukemias.